Approach to effectiveness evaluation of innovation mechanism of industrial enterprises - Дунська, Алла Рашидівна (Technology audit and production reserves, 2015)
The innovative mechanism of industrial enterprises should be considered as a system of interrelated elements, combination and simultaneous operation of which will contribute to the development of innovative enterprises. The study of innovative mechanisms to date remains one of the least concretized in the areas of innovation management. The introduction of the concept of enterprise innovation mechanism requires specification of approaches to assessing its effectiveness. To solve this problem, it was suggested to structure of innovative mechanism of industrial enterprise on five main elements, namely: 1) the mechanism of diagnosis; 2) the mechanism of action; 3) the mechanism of providing; 4) the mechanism of transformation; 5) the mechanism of interaction. To assess the effectiveness of certain elements in the structure of innovative mechanisms have been proposed calculation factors which determine the nature of the processes that ensure every element of innovation mechanism. It is proposed evaluating the efficiency of the innovative elements after normalization of calculated coefficients to perform functions on the basis of desirability. The article reviews the intervals for evaluation of coefficients for seven types of innovative mechanisms. Applying the proposed approach to evaluating the effectiveness of the mechanism will allow innovative level of subjectivity in making management decisions.